The Development of Byron’s Philosophy of Knowledge - Jackson, Emily A. Bernhard. author. aut Link
XI, 229 p.
Keywords: Taking a fresh approach to Byron, this book argues that he should be understood as a poet whose major works develop a carefully reasoned philosophy. Situating him with reference to the thought of the period, it argues for Byron as an active thinker, whose final philosophical stance - reader-centred scepticism - has extensive practical implications.